Diagnostic accuracy of endoscopic trimodal imaging and chromoendoscopy for lesion characterization in ulcerative colitis - Vleugels, JLA; Rutter, MD; Ragunath, K; Rees, CJ; Ponsioen, CY; Lahiff, C; Ket, SN; Wanders, LK; Samuel, S; Butt, F; Kuiper, T; Travis, SPL; et al. (Oxford University Press, 2018)
Background Patients with longstanding ulcerative colitis (UC) are at increased risk for developing CRC. During surveillance colonoscopy, a variety of dysplastic and non-dysplastic lesions are detected. The aim of this study was to address the diagnostic accuracy of endoscopic differentiation autofluorescence imaging (AFI), narrow band imaging (NBI) and chromoendoscopy (CE). Methods This is a pre-specified additional analysis of a multicentre randomised controlled trial that compared AFI with CE for dysplasia detection in 210 patients with longstanding UC (FIND-UC trial). In the AFI arm, endoscopists recorded AFI color and Kudo pit pattern using NBI. Kudo pit pattern was described in the CE arm. For AFI, purple colour and ambiguous colour combined with pit pattern type III-V on NBI was considered dysplastic. For pit pattern description using NBI and CE, type III-V was considered dysplastic. Histology was the reference standard; sessile serrated lesions without dysplasia were considered non-dysplastic. Results In total, 52 dysplastic and 255 non-dysplastic lesions were detected. Overall sensitivity for real-time prediction of dysplasia was 76.9% (95% confidence interval (CI) 46.2-95.0) for NBI and AFI combined, and 81.6% (95% CI 65.7-92.3) for CE (p=0.72). For high confidence predictions, negative predictive value (NPV) of the combination of AFI and NBI was 97.7% (95% CI 92.4-99.3) versus 97.4% (95% CI 90.2-97.2) for CE (p=0.41). Interpretation Sensitivity for endoscopic differentiation of dysplastic lesions detected during surveillance of patients with longstanding UC seems limited. The high NPV using these techniques may be sufficient to leave suspected non-dysplastic lesions in situ without biopsy (NTR4062).